2012
DOI: 10.1289/ehp.1103743
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Organochlorine Pesticides and Growth among Russian Boys

Abstract: Background: Limited human data suggest an association of organochlorine pesticides (OCPs) with adverse effects on children’s growth.Objective: We evaluated the associations of OCPs with longitudinally assessed growth among peripubertal boys from a Russian cohort with high environmental OCP levels.Methods: A cohort of 499 boys enrolled in the Russian Children’s Study between 2003 and 2005 at 8–9 years of age were followed prospectively for 4 years. At study entry, 350 boys had serum OCPs measured. Physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 50 publications
1
40
0
1
Order By: Relevance
“…These findings are in line with previous reports [14,44] in which individuals that were regularly exposed to carbamates and endosulfan reported reproductive and erectile dysfunction. In addition, Burnett [45] in his review reports increased erectile dysfunction and loss of libido in men exposed to a variety pesticides [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous reports [14,44] in which individuals that were regularly exposed to carbamates and endosulfan reported reproductive and erectile dysfunction. In addition, Burnett [45] in his review reports increased erectile dysfunction and loss of libido in men exposed to a variety pesticides [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Of possible relevance, an inverse association has been reported between arsenic exposure and the plasma concentration of insulin-like growth factor 1 in preschool children (Ahmed et al 2013). Adverse effects of environmental exposure to metals, such as lead and cadmium, on children's growth and insulin-like growth factor 1, support the notion that developmental exposures can affect height achieved at adult age (Afeiche et al 2012;Burns et al 2012;Fleisch et al 2013;Gardner et al 2013). …”
Section: Discussionmentioning
confidence: 92%
“…[2] No studies investigating the effect of currently registered agricultural pesticides on pubertal growth were found in the literature, but there is laboratory and epidemiological evidence of reduced height measurements among DDT-exposed boys, although results are contradictory, as discussed earlier. [6][7][8][9][10] …”
Section: Discussionmentioning
confidence: 99%
“…[9] A recent Russian cohort study of 499 boys aged 8 -9 years revealed lower mean BMI and height Z-scores associated with p,p'-DDE. [10] This contradictory epidemiological evidence in the literature of the effects of pesticides on pubertal development of boys requires further investigation.…”
mentioning
confidence: 99%